Regularity for 3D Inhomogeneous Naiver–Stokes Equations in Vishik Spaces. (12th March 2022) - Kim, Jae-Myoung
Abstract : In this short paper, we consider the conditional regularity for the 3D inhomogeneous incompressible Navier–Stokes equations in Vishik spaces and give regularity criterion of strong solutions.